Neuromechanics of middle-distance running fatigue: A key role of the plantarflexors? - Willer, J.; Allen, S. J.; Burden, R. J.; Folland, J. P. (Medicine & Science in Sports & Exercise, 2021)
Purpose: This study aimed to investigate the changes in lower limb kinematics, kinetics, and muscle activation during a high-intensity run to fatigue (HIRF). Methods: Eighteen male and female competitive middle-distance runners performed a HIRF on an instrumented treadmill at a constant but unsustainable middle-distance speed (~3 min) based on a preceding maximum oxygen uptake (V?O2max) test. Three-dimensional kinematics and kinetics were collected and compared between the start, 33%, 67%, and the end of the HIRF. In addition, the activation of eight lower limb muscles of each leg was measured with surface EMG (sEMG). Results: Time to exhaustion was 181 ± 42 s. By the end of the HIRF (i.e., vs the start), ground contact time increased (+4.0%), whereas flight time (-3.2%), peak vertical ground reaction force (-6.1%), and vertical impulse (-4.1%) decreased (all P < 0.05), and joint angles at initial contact became more (dorsi)flexed (ankle, +1.9°; knee, +2.1°; hip, +3.6°; all P < 0.05). During stance, by the end of the HIRF: peak ankle plantarflexion moment decreased by 0.4 N·m·kg-1 (-9.0%), whereas peak knee extension moment increased by 0.24 N·m·kg-1 (+10.3%); similarly, positive ankle plantarflexion work decreased by 0.19 J·kg-1 (-13.9%), whereas positive knee extension work increased by 0.09 J·kg-1 (+33.3%; both P < 0.05) with no change in positive hip extension work. Hip extensor surface EMG amplitude increased during the late swing phase (+20.9-37.3%; P < 0.05). Conclusion: Running at a constant middle-distance pace led primarily to the fatigue of the plantarflexors with a compensatory increase in positive work done at the knee. Improving the fatigue resistance of the plantarflexors might be beneficial for middle-distance running performance.